2009
DOI: 10.1177/1074248409350136
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Reduces Oxidative Stress, but not Aortic Damage in Atherosclerotic Rabbits

Abstract: We evaluated whether carotenoid astaxanthin (ASX) could prevent oxidative and atherosclerotic damage in rabbits. Rabbits received regular chow (control) or an atherogenic diet (1% cholesterol) alone or supplemented with 50, 100, and 500 mg% ASX for 60 days (n = 5-9 per group). The atherogenic diet increased the serum cholesterol levels and the ratio of the intima/media area in the aortic arch. These changes were not prevented by ASX. Atherosclerotic rabbits showed increased aortic lipid peroxidation and nonpro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Elevated plasma cholesterol levels play a dominant role in cardiovascular diseases [1] as can be evidenced by the occurrence of atheroma in the aorta of hypercholesterolemic rabbits [14]. Accordingly, the AI, which reflects the relationship between the non-HDL cholesterol fraction and the HDL cholesterol fraction and is considered a possible indicator of a predisposition to heart disease [15], was directly correlated to the increase in LDL levels.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated plasma cholesterol levels play a dominant role in cardiovascular diseases [1] as can be evidenced by the occurrence of atheroma in the aorta of hypercholesterolemic rabbits [14]. Accordingly, the AI, which reflects the relationship between the non-HDL cholesterol fraction and the HDL cholesterol fraction and is considered a possible indicator of a predisposition to heart disease [15], was directly correlated to the increase in LDL levels.…”
Section: Discussionmentioning
confidence: 99%
“…(16) Since ASX is carried in serum and hypercholesterolemia is an important event in atherosclerosis, the knowledge of ASX effects on the lipids and oxidative stress in the serum will complement previous data on the aortic tissue. Furthermore, the possible protective role of ASX on PON1 activity during experimental hypercholesterolemia has not been investigated.…”
Section: Introductionmentioning
confidence: 89%
“…ASX had no protective effect against LDL oxidation and atherosclerotic lesions in Watanabe heritable hyperlipidemic rabbits (15) or against aortic damage in atherosclerotic New Zealand rabbits. (16) However, ASX prevented the oxidation of human LDL in vitro (17) and stabilised atherosclerotic plaques in rabbits. (18) …”
Section: Introductionmentioning
confidence: 99%
“…Pashkow et al [69] suggested that there might be a potential therapeutic role for astaxanthin in the management of myocardial injury, oxidized low-density lipoprotein, and rethrombosis after thrombolysis, as well as other cardiac diseases such as atrial fibrillation. Augusti et al [77] indicated that although astaxanthin did not prevent hypercholesterolemia or atherosclerotic lesions caused by the atherogenic diet in rabbits, it could play a beneficial role by preventing lipid peroxidation and changes in antioxidant enzyme activities.…”
Section: Cardiovascular Protective Effectmentioning
confidence: 98%